Концепт дороги в художественном пространстве поэзии Иосифа Бродского - Модылина, М. (Літературознавчі обрії. Праці молодих учених, 2010)
In the given article an attempt is made to examine the peculiarities of the concept of road in the poetry by J. Brodsky and to study the specific features of its application and philosophical interpretation. The author points out three main directions in which the poet’s thought was developing and the concept of road found its representation. The author of the paper also says about the possibility for this concept to be embodied in different contextual synonyms, such as stairs, street, blind alley etc. which can be found in J. Brodsky’s poetry.